An assessment of bacterial transmission via rebound tonometry: An in vitro pilot study - Jonathan Alexander Wood; Martyn King; Anita Dutton (Open Veterinary Journal)
Background: Bacterial contamination of medical equipment is a significant risk in both human and veterinary medicine, leading to potential cross-contamination between clinicians, technicians, patients, and healthcare professionals. Pathogens can persist on surfaces, resulting in healthcare-associated infections. Tonometry used to measure intraocular pressure (IOP) for diagnosing conditions like glaucoma and uveitis, is crucial in both human and veterinary care. However, there is limited information on bacterial transmission through reused tonometer probes in veterinary patients. This pilot study aimed to explore the potential for cross-contamination of bacteria via a rebound tonometer probe using bacterial isolates linked to bacterial ulcerative keratitis in dogs.